Implications of Job Satisfaction on Productivity through Work Motivation, Work Environment, and Internal Communication in Serpong Building Depot Employees - Debora Hutagalung; Udin Ahidin; Rosa Lesmana (Indonesian Development of Economics and Administration Journal, 2025)
This study aims to analyze the effect of job satisfaction on employee productivity through work motivation, work environment, and internal communication among employees of Depo Bangunan Serpong. In facing increasingly intense competition in the building materials retail industry, companies are required to enhance employee productivity as a key factor for organizational success. Employee productivity is influenced not only by technical factors and work systems, but also by psychological aspects and the work environment that shape job satisfaction. The hypothesis testing results indicate that work motivation has a positive and significant effect on productivity, the work environment has a positive and significant effect on productivity and internal communication also has a positive and significant effect on productivity. Work motivation, work environment and internal communication also have positive and significant effects on job satisfaction. Furthermore, job satisfaction has a positive and significant effect on employee productivity. The mediation test results show that job satisfaction mediates the effect of work motivation on productivity the effect of the work environment on productivity, and the effect of internal communication on productivity. These findings indicate that improving employee productivity can be optimally achieved through enhancing job satisfaction supported by strong work motivation, a conducive work environment, and effective internal communication.